How to find the right job or, at least, avoid the failure of choosing the wrong one (Journal of EAHIL, 2019)
This paper aims to help medical librarians spot potential friction with a would-be employer. This is achieved by naming the most important aspects to focus on while choosing a new position, in order to avoid disappointment in a new role. It summarises anecdotal evidence based on personal experience.